PENGETAHUAN DAN SIKAP IBU TERHADAP KEKERASAN SEKSUAL PADA ANAK - Dini Rakhmawati; Yovitha Yuliejatiningsih; Desi Maulia (Universitas PGRI Semarang, 2017)
Sexual violence lately has been lurking early childhood. Mother's knowledge on sexual violence is necessary to understand, characterize, type, and prevention efforts, mothers have an attitude to support prevention of sexual violence in early childhood. This Research used Cross sectional method. The number of samples is 212 with purposive sampling technique. Data analysis using pearson correlation test. The results of trials in 212 respondents in four sub-districts in Gunung Pati sub-district showed that the higher the mother's knowledge of sexual violence in children, the higher the prevention attitude toward sexual violence in children. Vice versa, the lower the knowledge of the mother the lower the prevention attitude toward sexual violence in early childhood. Keywords: Knowledge, attitude, sexual violence in children.